2005
DOI: 10.1107/s0108768105022585
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoepitaxial transrotational structures in 14 nm-thick NiSi layers on [001] silicon

Abstract: In a system consisting of two different lattices, the structural stability is ensured when an epitaxial relationship occurs between them and allows the system to retain the stress, avoiding the formation of a polycristalline film. The phenomenon occurs if the film thickness does not exceed a critical value. Here we show that, in spite of its orthorombic structure, a 14nm-thick NiSi layer can threedimensionally (3D) adapt to the cubic Si lattice by forming transrotational domains. Each domain arises by the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 15 publications
1
20
0
1
Order By: Relevance
“…One of those bending contour (b1), which is the most representative one, originates from the (020) NiSi planes which are known to be anchored to (220) Si planes through the layer/substrate interface. 9 It was found 9 that a 618 continuous rotation of the orthorombic NiSi lattice around the direction normal to the (020) planes moves the lattice configuration from the [102] to the [201] zone axis passing through [101] without meeting other relevant axes in between. This causes the domains to have just those three selective zone axes (identifying the crystallographic axis perpendicular to the interface), and, thus, to be of just three different types.…”
mentioning
confidence: 99%
“…One of those bending contour (b1), which is the most representative one, originates from the (020) NiSi planes which are known to be anchored to (220) Si planes through the layer/substrate interface. 9 It was found 9 that a 618 continuous rotation of the orthorombic NiSi lattice around the direction normal to the (020) planes moves the lattice configuration from the [102] to the [201] zone axis passing through [101] without meeting other relevant axes in between. This causes the domains to have just those three selective zone axes (identifying the crystallographic axis perpendicular to the interface), and, thus, to be of just three different types.…”
mentioning
confidence: 99%
“…Alberti et al observed the formation of so-called "transrotational" domains, both in Ni 2 Si and NiSi films. 49,111 These domains result from a bending (either spherical or cylindrical) of specific crystallographic planes of the film in order to adapt to the crystal structure of the substrate. 49 This transrotational NiSi has been observed to form under different experimental conditions (annealing ambient, substrate doping, etc.)…”
Section: Nisimentioning
confidence: 99%
“…49,111 These domains result from a bending (either spherical or cylindrical) of specific crystallographic planes of the film in order to adapt to the crystal structure of the substrate. 49 This transrotational NiSi has been observed to form under different experimental conditions (annealing ambient, substrate doping, etc.) as long as specific care is taken during the deposition of the initial Ni film: the Ni must be deposited at slightly elevated temperatures in order to obtain a Ni-rich intermixed Ni:Si layer and when the thickness of the deposited Ni surpasses $7 nm, a low temperature isothermal anneal is necessary to form transrotational NiSi.…”
Section: Nisimentioning
confidence: 99%
“…10) It was found that the layer has a transrotational structure. 6) The structure of a transrotational domain, as shown in the TEM plan-view image of Fig.…”
mentioning
confidence: 99%
“…We have additionally shown 7) that the composition of the precursor layer can be also modified by slightly increasing the deposition temperature. A 6 nm precursor layer (amorphous), with a Ni:Si concentration ratio of $3, can be formed on an oxygen-free Si substrate by depositing nickel atoms at $50 C. 8) From the amorphous mixed layer first transrotational Ni 2 Si 9) and, subsequently, transrotational NiSi domains originate 10,11) during lowtemperature annealing (e.g., 260 C).…”
mentioning
confidence: 99%